FREE, PRIOR AND INFORMED CONSENT IN FULFILLING THE CONSTITUTIONAL RIGHTS OF CITIZENS IN THE MINING SECTOR - Harliansyah, Harliansyah; Rini, Astiti Swanita; Siagian, Eva Nopitasari; Andjab, Tuntas Karawahno; Fall, Rokhaya (Scholar Center, 2021)
Based on data from the Directorate General of Mineral and Coal, Ministry of Energy and Mineral Resources, in 2017, there are 9,353 Mining Business Licenses (MBL) with 9,074 MBLs entered in the DG of Mineral and Coal database. Of these, 6,565 MBLs passed the CnC requirements, while the remaining 2,509 MBLs were categorized as non-CnC. The focus of the problems studied are: (1) What is the Direction of Changes in Government Policy in the Mining Sector? (2) What is the relationship between Free, Prior and Informed Consent with the fulfillment of the constitutional rights of citizens in the mining sector? The method used in this study is doctrinal legal research focusing on sources of law. The result shows that (1) There are changes in government policy in the mining sector, which was only constrained in its implementation, but has now become more problematic because of the removal of the article on the imperative community participation; (2) In every policy setting, FPIC must be implemented and must be given to the community, especially those who are directly affected. Thus, FPIC can be said to be a form of community rights that must be fulfilled by the government as the licensor legally to fulfill the constitutional rights of its citizens.